Karakteristik Cokelat Praline dengan Penambahan Jeruk Siam Kintamani Sebagai Bahan Pengisi - Sitiari, I Gusti Ayu; Permana, I Dewa Gde Mayun; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPA, 2024)
Praline chocolate is a chocolate product with the addition of fillers such as fruits or nuts. The praline chocolate industry is experiencing challenges related to the innovation of fillers. This problem can be overcome by adding oranges as fillers to add innovation through increasing the distinctive citrus taste and aroma. The purpose of this study is to determine the effect of the addition of Kintamani siameseorange as a filler on the characteristics of praline chocolate and to obtain the right concentration of adding Kintamani siamese orange as a filler to praline chocolate. This study used a Complete Random Design (RAL) with the addition of Kintamani Siamese as a filler, namely 10%, 15%, 20%, 25%, 30%, and 35%. Each treatment was repeated three times, there were 18 experimental units. The data was analyzed with analysis of variance, if the treatment had a effect on the observed parameters continued with Duncan's Multiple Range Test (DMRT). The parameters observed were water content, ash content, fat content, vitamin C levels, total acid and sensory evaluation. The results showed the addition of Kintamani Siamese orange had a real effect on water content, ash, fat, vitamin C, total acid, color hedonic and overall acceptance,the best treatment with the addition of Kintamani siamese orange as a filler of 20% with water content of 12,32%, ash content of1,64%, fat content of 37,43%, vitamin C content of 7,77 mg /100g, total acid of 0,72% with color, aroma, textures with rather harsh criteria, flavors with slightly sweet criteria, and overall acceptance is favored by panelists. Keywords: Filler ingredients, chocolate praline, Siamese orange Kintamani